International Graduate Colloquium: Sports and Physical Exercise Assembly of Knowledge Sharing, i-SPEAK 2025, Series 1 / Faculty of Sports Science and Recreation UiTMCNS Kampus Seremban - UiTM, Faculty of Sports Science and Recreation UiTMCNS Kampus Seremban (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Publisher Universiti Teknologi MARA (UiTM), Negeri Sem¬bilan Branch, Seremban Campus, Faculty of Sports Science and Recreation, Persiaran Seremban Tiga/1, Seremban 3, 70300 Seremban. MALAYSIA. This work is subject to copyright. All rights are reserved by the publisher, whether the whole or part of the material is concerned, specifically the rights of translation, reprinting, reuse of illustra¬tions, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by sim¬ilar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trade¬marks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a warranty, expressed or implied, with respect to the material contained herein or for any errors or omissions that may have been made. The publisher remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.